Semi-structured interviews in qualitative research in education - Oliveira, Silvaney de (2023)
This article presents a qualitative approach research of the bibliographical type of interpretative nature carried out in articles, books, theses, and dissertations on the semi-structured interview as a data collection instrument. It aimed to describe and indicate the possibility of conducting the semi-structured interview in investigations in the field of education. From the research carried out, it was possible to detail stages for the design and execution of interviews in educational research. It was also identified the importance of the criteria used to build the script and the interactive character of the dialogue carried out during the interviews to allow access to the meanings attributed by the research participants to the investigated phenomenon.